2009
DOI: 10.1116/1.3168563
|View full text |Cite
|
Sign up to set email alerts
|

Defect-mediated adsorption of methanol and carbon dioxide on BaTiO3(001)

Abstract: The surface chemistry of single crystal barium titanate (BaTiO3) has been studied using temperature programmed desorption (TPD). TPD measurements were performed with several probe molecules, including methanol and carbon dioxide. The role of oxygen vacancies in the adsorption and reaction of these molecules was examined by annealing the crystal under oxidizing or reducing conditions prior to performing TPD. It is shown that the adsorption and reaction of methanol and carbon dioxide are enhanced on BaTiO3(001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This variation in the energy levels at the surface dramatically influences chemical reactivity. We and others have shown that molecular adsorption is domain specific in a number of systems 21–25. Domain specific photo oxidation and reduction have been demonstrated in liquids, and a range of metal and metal oxide nanoparticles have been produced in a domain specific manner 26–30.…”
Section: Polarization Dependent Reactionsmentioning
confidence: 94%
“…This variation in the energy levels at the surface dramatically influences chemical reactivity. We and others have shown that molecular adsorption is domain specific in a number of systems 21–25. Domain specific photo oxidation and reduction have been demonstrated in liquids, and a range of metal and metal oxide nanoparticles have been produced in a domain specific manner 26–30.…”
Section: Polarization Dependent Reactionsmentioning
confidence: 94%
“…The chemical stability and reactivity of oxide materials are largely controlled by defects and impurities, and experimental studies are complicated by the presence of surface defects (Garra et al, 2009). Typical defects in oxides are point defects (missing atoms, e.g.…”
Section: Figurementioning
confidence: 99%
“…Apart from water, the interaction of various molecules (CO, NO, alcohols, etc.) with these materials has also been considered, especially to assess the effect of surface polarization . This effect is small but can significantly modify the bonding strength in some cases.…”
Section: Introductionmentioning
confidence: 99%